2017
DOI: 10.1080/09553002.2017.1377360
|View full text |Cite
|
Sign up to set email alerts
|

Role of NADPH oxidase in radiation-induced pro-oxidative and pro-inflammatory pathways in mouse brain

Abstract: Purpose: The present study was designed to investigate our hypothesis that NADPH oxidase plays a role in radiation-induced pro-oxidative and pro-inflammatory environments in brain. Materials and Methods: C57BL/6 mice received either fractionated whole brain irradiation or sham-irradiation. The mRNA expression levels of pro-inflammatory mediators, such as TNF-α and MCP-1, were determined by quantitative real-time RT-PCR. The protein expression levels of TNF-α, MCP-1, NOX-2 and Iba1 were detected by immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…In animal model, it has shown that upregulation of prooxidant enzymes such as NOX1, NOX4, COX-2, iNOS and also increased superoxide production by mitochondria are involved in the development of pneumonitis and fibrosis [25][26][27]. Similar results have shown for intestinal cells, vascular endothelial cells, mice brain, etc [28][29][30].…”
Section: Molecular Mechanisms For Continuous Ros Production Followingsupporting
confidence: 58%
“…In animal model, it has shown that upregulation of prooxidant enzymes such as NOX1, NOX4, COX-2, iNOS and also increased superoxide production by mitochondria are involved in the development of pneumonitis and fibrosis [25][26][27]. Similar results have shown for intestinal cells, vascular endothelial cells, mice brain, etc [28][29][30].…”
Section: Molecular Mechanisms For Continuous Ros Production Followingsupporting
confidence: 58%
“…One of the critical pathways triggered by γ-radiation is the apoptotic pathway that could be resulted from DNA damage and oxidative stress. The intrinsic pathway is activated at the mitochondrial level, which subsequently triggers follicular apoptosis by caspases activation 42 . The follicular apoptosis is regulated both by pro-apoptotic factors (e.g., Bax) and anti-apoptotic factors (e.g., Bcl-2 and anti-oxidative agents) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS can be derived from different sources, including the mitochondria electron transport chain, xanthine oxidase, the cytochrome P450 system, uncoupled nitric oxide synthase, and myeloperoxidase. ROS also mainly comes from two main parts, mitochondrial and NADPH oxidase after radiation ( Bedard and Krause, 2007 ; Bhattacharyya et al., 2014 ; Cho et al., 2017 ; Pei et al., 2017 ; Kawamura et al., 2018 ; Sakai et al., 2018 ; Shimura et al., 2018 ; Mortezaee et al., 2019 ). To explore the origin of ROS induced by 1α,25(OH) 2 D 3 , both NADPH oxidase inhibitors, DPI and Apocynin, and the mitochondrial membrane potential were used to determine the source of ROS ( Bedard and Krause, 2007 ).…”
Section: Discussionmentioning
confidence: 99%